Surface induces different crystal structures in a room temperature switchable spin crossover compound. Issue 1 (17th November 2015) - Gentili, Denis; Liscio, Fabiola; Demitri, Nicola; Schäfer, Bernhard; Borgatti, Francesco; Torelli, Piero; Gobaut, Benoit; Panaccione, Giancarlo; Rossi, Giorgio; Degli Esposti, Alessandra; Gazzano, Massimo; Milita, Silvia; et al.
Abstract : We investigated the influence of surfaces in the formation of different crystal structures (polymorphs) of a room temperature switchable spin crossover compound. Abstract : We investigated the influence of surfaces in the formation of different crystal structures of a spin crossover compound, namely [Fe(L)2 ] (LH: (2-(pyrazol-1-yl)-6-(1 H -tetrazol-5-yl)pyridine), which is a neutral compound thermally switchable around room temperature. We observed that the surface induces the formation of two different crystal structures, which exhibit opposite spin transitions, i.e. on heating them up to the transition temperature, one polymorph switches from high spin to low spin and the second polymorph switches irreversibly from low spin to high spin. We attributed this inversion to the presence of water molecules H-bonded to the complex tetrazolyl moieties in the crystals. Thin deposits were investigated by means of polarized optical microscopy, atomic force microscopy, X-ray diffraction, X-ray absorption spectroscopy and micro Raman spectroscopy; moreover the analysis of the Raman spectra and the interpretation of spin inversion were supported by DFT calculations.